Induction of porcine‐specific regulatory T cells with high specificity and expression of IL‐10 and TGF‐β1 using baboon‐derived tolerogenic dendritic cells. (22nd October 2017) - Li, Mingqian; Eckl, Judith; Abicht, Jan‐Michael; Mayr, Tanja; Reichart, Bruno; Schendel, Dolores J.; Pohla, Heike
Abstract: Background: Regulatory T cells (Treg) play an important role in maintenance of homeostasis in vivo. Treg application to alleviate allo‐organ rejection is being studied extensively. However, natural Treg (nTreg) expansion in vitro is laborious and expensive. Antigen‐specific Treg are more effective and require lower cell numbers than use of nTreg for immune control. The baboon, as a non‐human primate experimental animal model, is widely used in xenotransplantation research. An effective method to generate baboon xeno‐specific Treg would benefit research on immune tolerance in xenotransplantation using this model system. Method: Baboon tolerogenic dendritic cells (tolDC) were generated in 3 days from monocytes isolated from baboon peripheral blood mononuclear cells in medium supplemented with anti‐inflammatory cytokines. After loading with porcine‐specific (PS) in vitro‐transcribed RNA (ivtRNA), tolDC were used to induce CD4 + T cells to become porcine‐specific Treg (PSTreg) in cocultures supplemented with IL‐2 and rapamycin for 10 days. Anti‐inflammatory and inflammatory cytokine expression was evaluated at the mRNA and protein levels in both baboon tolDC and PSTreg. Functional assays, suppression of activation markers on porcine‐specific effector T cells (PSTeff) and inhibition of PSTeff proliferation, were used to test PSTreg specificity. Results: TolDC generated with this method exhibited a tolerogenic phenotype, expressed CCR7 and produced high levels of IL‐10 and TGF‐β1, whereas IL‐12p40 and IFN‐γ were not expressed. PSTreg were successfully generated in cocultures of CD4 + T cells and PS ivtRNA‐loaded tolDC. They exhibited a CD3 +  CD4 +  CD25 +  CD127 low/−  CD45RA low  Foxp3 + phenotype and were characterized by high expression of IL‐10 and TGF‐β1 mRNA and protein. They showed upregulated expression of EBI3 and GARP mRNA. PSTreg exhibited highly suppressive effects toward PSTeff, secreting high amounts of IL‐10 and TGF‐β1 cytokine upon interaction with PSTeff and suppressing IFN‐γ expression on PSTeff. Conclusion: In this study, a fast 3‐day method to generate baboon‐derived tolDC is provided that allows subsequent induction of PSTreg displaying high porcine‐antigen specificity and expression of IL‐10 and TGF‐β1. Porcine‐specific baboon Treg can be used in porcine solid organ or cell xenotransplantation studies through adoptive cell transfer into host baboons.